27th Annual APRN Legislative Update. Issue 1 (16th January 2015) - Phillips, Susanne J.
<x xml:space="preserve">Abstract</x> As the tides of healthcare in the United States continue to change, advanced practice registered nurses (APRNs) are at the forefront of legislative history. This overview provides a snapshot of legislative and regulatory activity in 2014 as reported by state Boards of Nursing and nursing organizations representing APRNs.